Beyond A love supreme : John Coltrane and the legacy of an album - Whyton, Tony (Oxford University Press, 2013)
John Coltrane's A Love Supreme is widely considered one of the greatest jazz albums of all time. In Beyond A Love Supreme, author Tony Whyton explores both the musical aspects of A Love Supreme, and the album's seminal importance in jazz history, as well as its broader musical and cultural impact.